FORMATION OF PERSONALITY TRAITS OF ADOLESCENCES IN EDUCATION ENVIRONMENT - Farajova, Narmin (Revista Gênero e Interdisciplinaridade, 2024)
The educational environment significantly impacts the formation of personality features in adolescence. Schools can help adolescents develop into well-rounded, resilient, and capable individuals by fostering a supportive, inclusive, and stimulating atmosphere. Effective education policies and practices should consider the holistic development of pupils, addressing not just academic achievement but also social, emotional, and personal growth.